User Experience Design Sales Performance and Sales Person Productivity Application MTFSales Using Human Centered Design Method (Case Study: PT Mandiri Tunas Finance) - Eldi Romadhona, Safira; Rokhmawati, Retno Indah; Priharsari, Diah (Journal of Information Technology and Computer Science, 2023)
PT Mandiri Tunas Finance is a company engaged in financing new or used cars, motorcycles, and commercial vehicles, with a network of 102 branches spread throughout Indonesia. In its business process, sales performance monitoring is still considered ineffective, because the information about sales performance is in the form of an excel calculated manually. The salesperson could not monitor it directly. This study aims to produce a MTFSales application design using Human Centered Design. The prototype was tested using the user testing method and the SUPR-Q questionnaire. The results of the test using user testing are positive results with some suggestions from users. The test results using the SUPR-Q method for sales officers are 88.19%, sales heads are 88.65% and branch managers are 83.81%. All three are in the excellent and acceptable categories so it can be said that the design can be accepted by the users.